Evaluasi Nilai Noise Sebelum Dan Sesudah Kalibrasi Sebagai Salah Satu Wujud Kinerja Pesawat CT-Scan - Andrey Nino Kurniawan Nino Kurniawan; Indah Soesanti Soesanti (Forum Teknik, 2010)
The noise has to be measured daily because it directly degrades image quality, which inturn it is dificult to define between normal and pathological tissues on a-CT image. Thisresearch’s aim was performed to examine noise differences between before and aftercalibrating of the CT-scanner system, and also to study the chance of noise deviated values day-by-day during 20 days of the two different periods of measurement.A callibrated head water phantom was scanned before and after equipment callibrations,using the head scanning parameter, and device measurement at ROI 228.2 mm2 to obtain thenoise data. Descriptive statistics was employed to present related information, and the T-testpaired-sample was the statistical tool to test the null hypothese (Ho) with level of significance(α) 0.05.The results showed most of noise values between before and after equipment calibrationsfall arround the base line or within two standard deviation (2SD). In before callibration of thenoise, the base line noise value is 4.76 HU whereas the upper limit and the lower limmit of thenoise values are 5.34 HU and 4.18 HU (respectively) with a-1.16 HU difference. In aftercallibration of the noise, the base line noise value is 4.35 HU whereas the upper limit and thelower limmit of the noise values are 5.29 HU and 3.41 HU with a-1.87 HU difference. However,there are two out of fourty noise values (± 5%) that fall outside of the 2SD limmit if a numberfalls outside of 2SD from the base line in the same direction (i.e., all high or all low) more thanfour days in a row, it is a shift that could be due to a machine malfunction and should beinvestigated before the outer control limit is exceeded. Statistical analyses with paired- sampleT-test showed p-value (0.005) < 0.05. By this meaning that, the noise between before and afterCT-Scanner callibrations are different in their values additonally most of the noise values aftercallibration seem to be low compared with that of the values before callibrations.Keywords: CT scan, evaluation, noise.